2020
DOI: 10.3390/ijerph17165647
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling and Coordinated Development from Urban Land Using Benefits and Urbanization Level: Case Study from Fujian Province (China)

Abstract: In recent years, urbanization has been developing rapidly. However, it is also accompanied by land management problems, such as low land use efficiency. In this research, we manage to explore the temporal and spatial evolution laws as well as characteristics of the coupling and coordinated development between urbanization and land use benefits. Through this, it is possible for us to provide policy recommendations for the sustainable development of the urbanization in Fujian Province. In this study, we take pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The degree of industrialization reflects the level of industrialization in a region and the environment in which enterprises produce their products. A higher level of industrialization will bring about an agglomeration effect, which will encourage enterprises to carry out green innovation activities to a certain extent [50]. The higher the proportion of the tertiary industry, the richer the industrial structure, and the higher the technological content [51,52], the better the innovation environment [53].…”
Section: Control Variablesmentioning
confidence: 99%
“…The degree of industrialization reflects the level of industrialization in a region and the environment in which enterprises produce their products. A higher level of industrialization will bring about an agglomeration effect, which will encourage enterprises to carry out green innovation activities to a certain extent [50]. The higher the proportion of the tertiary industry, the richer the industrial structure, and the higher the technological content [51,52], the better the innovation environment [53].…”
Section: Control Variablesmentioning
confidence: 99%
“…Zhou [11] and You et al [12] found that some local officials would develop the economy at the cost of the environment to improve their own political performance. Wang et al [13] also found that the level of land revenue in some Chinese cities is gradually declining. Land resources are important spatial carriers for urban production, living, and ecological activities as well as important input factors for socio-economic development [14].…”
Section: Introductionmentioning
confidence: 99%
“…As of 2014, the urban construction land of China has reached 49,882.7 km 2 [8]. The rapid growth of urban construction land usually comes at the expense of agricultural land and environmental land, which has caused new problems, such as the decline of ecological quality, land degradation, the increasingly prominent contradiction between human and land, and the decline of the overall benefit level of urban land use [9]. However, land-related income (land finance, etc.)…”
Section: Introductionmentioning
confidence: 99%